Competitive inhibition of TRPV1–calmodulin interaction by vanilloids - Winter, Zoltan; et al. (FEBS letters, 2016)
There is enormous interest toward vanilloid agonists of the pain receptor TRPV1 in analgesic therapy, but the mechanisms of their sensory neuron‐blocking effects at high or repeated doses are still a matter of debate. Our results have demonstrated that capsaicin and resiniferatoxin form nanomolar complexes with calmodulin, and competitively inhibit TRPV1–calmodulin interaction. These interactions involve the protein recognition interface of calmodulin, which is responsible for all of the cell‐regulatory calmodulin–protein interactions. These results draw attention to a previously unknown vanilloid target, which may contribute to the explanation of the paradoxical pain‐modulating behavior of these important pharmacons.<br
Keywords: vanilloid; TRPV1; capsaicin; resiniferatoxin; calmodulin